1997
DOI: 10.1097/00002030-199704000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Change in circulating levels of the chemokines macrophage inflammatory proteins 1α and 1β, RANTES, monocyte chemotactic protein-1 and interleukin-16 following treatment of severely immunodeficient HIV-infected individuals with indinavir

Abstract: The in vivo demonstration of an association between diminishing plasma HIV-RNA levels and the emergence of a circulating chemokine profile capable of inhibiting HIV replication corroborates recent in vitro observations and provides evidence for the restoration of chemokine capacity by HIV protease inhibitor-based therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
37
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 21 publications
6
37
2
Order By: Relevance
“…23 The broad-based antiproliferative effect favors the likelihood of inhibition of proteasomal activity, 21,22 or modulation of cytokine production. [33][34][35][36] Proteasomes are the main proteolytic complexes operating in the cytosol and nucleus and are involved in many biological and degradative processes. 37,38 The PI, Ritonavir, has been shown to block the chymotrypsin-like activity of murine 20S proteasome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The broad-based antiproliferative effect favors the likelihood of inhibition of proteasomal activity, 21,22 or modulation of cytokine production. [33][34][35][36] Proteasomes are the main proteolytic complexes operating in the cytosol and nucleus and are involved in many biological and degradative processes. 37,38 The PI, Ritonavir, has been shown to block the chymotrypsin-like activity of murine 20S proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Additionally, PIs have been reported to influence cytokines that regulate lymphocyte proliferation. [33][34][35][36]39,40 It has been shown that the serum levels of interleukin 16 (IL-16) are increased in patients on IDV-containing drug regimens. 35,36 IL-16 is known to inhibit anti-CD3-induced lymphocyte activation and lymphoproliferation.…”
Section: Discussionmentioning
confidence: 99%
“…As shownin this table, someaspects of gpl20-mediated T and B cell dysfunction are enhanced by cytokines, especially TNF-oc, derived from gp l 20-stimulated macrophages. Various events affecting in CD4+T cells, such as loss of CD4molecules (due to down-modulation or apoptosis), T cell receptor (TCR) inactivation, and blocking of conjugation between CD4and the major histocompatibility complex (MHC),as well as CD4+T cell anergy related to the activation (Table 1), mayinfluence the antigen recognition process and may be a significant factor in the decline of self-tolerance and the resultant induction of autoimmunity by HIV infection in addition to PBA.Interestingly, the changes of in vivo and/or in vitro cytokine and chemokine productions with the progression of HIV-1 infection are similar to those occurring in SLE with an increase of disease activity, including an increase in the production of T helper type 2 (Th2) cytokines and RANTES (regulated-upon activation, normal T expressed and secreted), as well as a decrease in the production ofT helper type 1 (Thl) cytokines and monocyte chemoattractant protein-1 (MCP-1) (42)(43)(44)(45). Such changes of cytokine and chemokine production are also regulated through stimulation by HIV envelope glycoprotein (46,47).…”
Section: Hiv and Autoimmunitymentioning
confidence: 87%
“…In addition a correlation between HIV-1 viremia and CCL2 levels has recently been shown in HIV-1 patients who develop atherosclerosis [47]. Finally, the importance of CCL2 in HIV pathogenesis is further observed since CCL2 levels along with plasma viral load have been shown to diminish in HIV-1 patients after indinavir (a viral protease inhibitor) treatment resulted in an improved response [48].…”
mentioning
confidence: 96%